2018
DOI: 10.14218/erhm.2018.00007
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of Autophagy-related Genes in Human Colon Cancer

Abstract: Background and objectives: Autophagy is a physiologic mechanism, which utilizes the self-digestion of cell organelles to promote cellular homeostasis, such as in the setting of dysfunctional cellular components, cellular stress or energy-deprived states. In vitro studies have pointed toward the key role of autophagy in colorectal cancer. However, in vivo studies from human colorectal cancer tissues are lacking. Methods: We collected tissue samples from six patients with colon cancer who received curative surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Lastly, we assessed different gene expression levels of the most common implicated genes in colorectal cancer after exposure to two types of general anesthesia with or without lidocaine. To our knowledge, only one study approached multiple autophagy-related genes (ATGs) in a pilot study where it was found that there was a different expression of multiple genes in the autophagy pathway in both early-and late-stage colorectal cancer and where several genes related to apoptosis such as BCL2 and CASP3 were down-regulated [33]. In our study, CASP 3 was increased in the SL group and decreased in the S group, while for the rest of the study groups, there were no significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we assessed different gene expression levels of the most common implicated genes in colorectal cancer after exposure to two types of general anesthesia with or without lidocaine. To our knowledge, only one study approached multiple autophagy-related genes (ATGs) in a pilot study where it was found that there was a different expression of multiple genes in the autophagy pathway in both early-and late-stage colorectal cancer and where several genes related to apoptosis such as BCL2 and CASP3 were down-regulated [33]. In our study, CASP 3 was increased in the SL group and decreased in the S group, while for the rest of the study groups, there were no significant differences.…”
Section: Discussionmentioning
confidence: 99%